Eksplorasi Pewarna Alami Di Vegetasi Hutan Resort Habaring Hurung Taman Nasional Sebangau Dengan Menggunakan Teknik Ecoprint: Exploration of Natural Dyes in the Forest Vegetation of Habaring Hurung Resort, Sebangau National Park, Using the Ecoprint Technique - Damanik, Mei Cintya Angelia; Tanduh, Yusintha; Misrita, Misrita; Afentina, Afentina; Koroh, Desy Natalia (HUTAN TROPIKA, 2025)
This study aims to identify vegetation species with potential as natural dyes and to describe the color direction, motif quality, and color fastness of ecoprint results using vegetation from the Habaring Hurung Forest Resort, Sebangau National Park. The research background is based on the biodiversity richness of peat swamp forests that has not been optimally utilized as a source of natural dyes in local wisdom-based creative industries. The ecoprint technique was selected for its eco-friendly nature and its ability to directly transfer the shape and natural color of leaves onto fabric. This research used a qualitative exploratory approach through field observation, interviews, documentation, and laboratory experiments. Vegetation sampling was conducted using a transect method covering an area of 0.4 hectares. The ecoprint process included mordanting, pounding, steaming, fixation, and color fastness testing. Color analysis referred to the Asianpaints color catalog, while motif quality was evaluated based on the visibility of leaf venation. The results identified 15 vegetation species with potential as natural dyes, including Tagula (Litsea sp.), Sepat (Macaranga trichocarpa), Mahang Kirik (Macaranga mauritia), and Kopi Himba (Coffea sp.). The dominant color directions produced were green, gray, and blue. The highest motif quality was found in Mahang Kirik, with clearly defined leaf veins, while the color fastness of most ecoprint fabrics remained stable after two washes. This indicates that the mordanting and fixation processes using iron mordant (tunjung) were effective in preserving color intensity. In conclusion, the peat forest vegetation in this area holds great potential as a source of natural dye for ecoprinting. These findings are expected to support the development of non-timber forest product (NTFP)–based crafts that promote forest conservation and empower surrounding communities.